Pengaruh Teknologi Visual Pengalaman Pengguna: Implikasi Terhadap Budaya Konsumsi dan Identitas Nasional - Fauzan, Muhammad Bilal; Saleh, Ade Rahmah; Figo, Muhammad Bias; Hidayat, Shosa; Bintang, Muhammad; Fadilah, Intan Nur (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Visual technology has become an integral part of the user experience in today's digital era. The use of visual technologies, such as images, videos, and graphics, has influenced the way individuals interact with digital content, products, and services. In the context of consumer culture, visual technology plays a significant role in shaping preferences, shopping behavior, and brand perceptions. The implications of the use of visual technology on consumer culture are seen in changes in people's consumption patterns, increased expectations for consumer experiences, and the evolution of more visually oriented marketing strategies. In addition, visual technology also has an impact on individuals' digital identities, where social media and online platforms become a place for self-expression through images and visual content.